O & L Jurutera Perunding Sdn. Bhd. / Nur Hidayah Hamim - Hamim, Nur Hidayah (Faculty of Civil Engineering, 2017)
Industrial training is an important phase of a student life. A well planned, properly executed and evaluated industrial training helps a lot in developing a professional attitude. It develop an awareness of industrial approach to problem solving, based on a broad understanding of process and mode of operation of organization. The aim and motivation of this industrial training is to receive discipline, skills, teamwork and technical knowledge through a proper training environment, which will help me, as a student in the field of Civil Engineering, to develop a responsiveness of the self-disciplinary nature of problem in engineering.